MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA MENGGUNAKAN MODEL STUDENT FACILITATOR AND EXPLANING DI KELAS IV SD NEGERI 060798 MEDAN AREA SELATAN - Harahap, Siti Zahara H. (Jurnal Tematik, 2018)
The objectives of this study are to observe whether : (1)knowing process  implementation of learning by using Student Facilitator and Explaining Model, (2) the improvement of learn mathematic result throughStudent Facilitator and Explaining Model by subject of FPB and KPK. This study was held at SD Negeri 060798 Medan Area Selatan by subject students of grade IV having 22 students. This study used classroom action research. The results showed that there was increase learn mathematic result studentsfrom cycle I to cycle II. Percentage increase learn mathematic result from cycle I to cycle II is 19,72% with average 59,24 increasing becaome 73,87.